A study of the rights of arrestees under selected laws in Malaysia / Fauziah Omar - Omar, Fauziah; Anak Dragam, Alpha; Abd Razak, Nor Azlina; Che Kar, Yurakasuma (2011)
This paper intends to explore the fundamental rights of the arrestees as provided for in the Federal Constitution as compared to a few selected laws such as the Criminal procedure Code and the Internal Security Act and the extent and the effectiveness of those rights being enforced by the authorities concerned. The qualitative type of research would be used whereby information will be gathered from selected statutes such as the Criminal Procedure Code and the Internal Security Act. On top of that, books will also be used as our source of reference. A semi structured interviews will also be conducted to get information from those involved. Decided cases also serve as an important source of reference for this research. The objectives of the study are to analyse the interpretation of the phrase as soon as may be as defined by the related statutes namely; the Criminal procedure Code and the Internal Security Act and decided cases and also the English language itself. It is also to analyse when the arrestees should be allowed to consult the legal representatives of their choice, be it before or after the arrest whether the provisions of the selected laws are synchronized with the Fundamental Liberties as provided for in Article 5 of the Federal Constitution. The limitations faced are due to the procedures and policies of the Police. The arrestees themselves might be hesitant in disclosing sensitive information as this might jeopardize their morale. They might also be afraid and may not be confident to disclose their experiences due to fear of being subjected to legal sanctions. On the other hand, it will also be difficult for the lawyers to meet the arrestee due to strict procedures to be adhered to such as the arrestees themselves are being transferred to different locations.